2007
DOI: 10.1017/s1751731107689757
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rate of substitution of processed, urea-treated whole-crop wheat for grass silage on the intake, milk production and diet digestibility in dairy cows and ruminal metabolism in vitro

Abstract: The effect of rate of substitution of processed, urea-treated whole-crop wheat (pWCW) for grass silage on intake, performance and whole-tract digestibility was evaluated using 44 dairy cows. Cows received 10.5 kg of concentrates per day and one of the following forage mixtures (dry matter (DM) basis): grass silage alone (W-0); 0.75 grass silage, 0.25 pWCW (W-25); 0.5 grass silage, 0.5 pWCW (W-50) or 0.25 grass silage, 0.75 pWCW (W-75). Forage DM intake increased linearly with inclusion rate of pWCW from 9.7 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Generally, whole crop cereal silage is considered to have lower digestibility and energy contents than that of high-quality grass silage (Hameleers,1998). The digestibilities of OM and NDF in the B1, M1 and M2 diets in the present experiment were similar to values (digestibility OM = 786 g kg − 1 , NDF = 720 g kg − 1 ) reported by Sinclair et al (2007) for a diet with similar concentrations of forage (grass silage only, ME = 10.9 MJ) and concentrate. Replacing a grass silage of 11 MJ with WCBS at heading is therefore possible, as long as the protein requirements of the dairy cows are met.…”
Section: Effect Of Mixing and Level Of Inclusionsupporting
confidence: 89%
See 1 more Smart Citation
“…Generally, whole crop cereal silage is considered to have lower digestibility and energy contents than that of high-quality grass silage (Hameleers,1998). The digestibilities of OM and NDF in the B1, M1 and M2 diets in the present experiment were similar to values (digestibility OM = 786 g kg − 1 , NDF = 720 g kg − 1 ) reported by Sinclair et al (2007) for a diet with similar concentrations of forage (grass silage only, ME = 10.9 MJ) and concentrate. Replacing a grass silage of 11 MJ with WCBS at heading is therefore possible, as long as the protein requirements of the dairy cows are met.…”
Section: Effect Of Mixing and Level Of Inclusionsupporting
confidence: 89%
“…They reported milk production similar to that obtained when the cows were fed diets with only grass silage as forage, provided that the WCBS proportion of the diet did not exceed 0.40 of forage DM (Bertilsson and Knicky, 2005;Ahvenjärvi et al, 2006). In another study, milk production was similar to the control treatment (grass silage only) when cows were fed late harvested, urea-treated whole crop wheat at 0.75 of forage DM (Sinclair et al, 2007). The aim of this experiment was to investigate the effect of maturity stage at harvest of WCBS, ranging from heading to early dough stage, on feed intake, diet digestibility and milk production by dairy cows.…”
Section: Introductionmentioning
confidence: 64%
“…It is has been demonstrated that mixing a second forage with grass silage results in an increase in DM intake (Phipps et al, 1995;Sinclair et al, 2007). Similarly, Salawu et al (2002), and Adesogan et al (2004), reported that midlactation cows fed pea-wheat intercrop silages had a forage DM intake that was higher than those fed grass silage alone.…”
Section: Animal Performancementioning
confidence: 97%
“…The antagonist supplemented diets were formulated to contain a total dietary concentration of approximately 3. diets were formulated to support a milk yield of approximately 38 kg/d according to Thomas (2004). Dietary ingredients were mixed using a forage mixer calibrated to ± 0.1 kg, with the resulting TMR being fed through roughage intake feeders (Hokofarm, Marknesse, Netherlands), fitted with an automatic weighing and animal identification system calibrated to ± 0.1 kg (Sinclair et al, 2007). Fresh feed was offered at 0900 h daily at 105% of the previous recorded intake, and refusals collected three times per week on a Monday, Wednesday and Friday.…”
Section: Animals Treatments Housing and Managementmentioning
confidence: 99%